2017
DOI: 10.21859/mci-supp-81
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Reproductive Risk Factors for Breast Cancer and Tumor Molecular Subtypes

Abstract: Introduction: Due to wide clinical differences in various pathological types of breast cancer and also close association between disease prognosis and molecular subtypes of the tumor, it has been recently suggested a relationship between traditional risk factors and molecular subtypes of breast cancer. Hence, the present study aimed to assess the association of reproductive risk factors for breast cancer with tumor molecular subtypes. Materials and Methods:This bi-center cross-sectional study was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…A study based on Iranian women found that a history of abortion was associated with luminal B breast cancer compared to other subtypes. 39 Another study among Northeastern Chinese women reported that spontaneous abortion was inversely associated with luminal A and luminal B subtypes, while induced abortion was associated with increased risk of luminal A tumors. 30 Further researches are warranted to clarify the effect of abortion on the stage and molecular subtypes of breast cancer and the potential underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study based on Iranian women found that a history of abortion was associated with luminal B breast cancer compared to other subtypes. 39 Another study among Northeastern Chinese women reported that spontaneous abortion was inversely associated with luminal A and luminal B subtypes, while induced abortion was associated with increased risk of luminal A tumors. 30 Further researches are warranted to clarify the effect of abortion on the stage and molecular subtypes of breast cancer and the potential underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated abortion for clinical stage of breast cancer, but studies on abortion and molecular subtypes reported controversial findings. A study based on Iranian women found that a history of abortion was associated with luminal B breast cancer compared to other subtypes . Another study among Northeastern Chinese women reported that spontaneous abortion was inversely associated with luminal A and luminal B subtypes, while induced abortion was associated with increased risk of luminal A tumors .…”
Section: Discussionmentioning
confidence: 99%
“…TNBC tumors make up 10-30% of all breast cancers and are reported to be the most aggressive form of BC with high histological grade, increased mitotic count, central necrosis and margins of invasion. It is also associated with younger age of incidence and poorer prognosis, in comparison to non-TNBC patterns 6 , as well as an association with shorter duration of breastfeeding, higher age at rst pregnancy and lower parity 7 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Therefore, exploration of the causes of recurrent abortion has important implications for the prevention and treatment of recurrent abortion. 8 In addition, other studies have shown that certain genetic polymorphisms are associated with breast cancer and may also be related to abortion, for example, the MDM2 Del1518 polymorphism and miR-196a (rs11614913). 6,7 Moreover, there are studies confirming that breast cancer may be associated with reproductive risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Moreover, there are studies confirming that breast cancer may be associated with reproductive risk factors. 8 In addition, other studies have shown that certain genetic polymorphisms are associated with breast cancer and may also be related to abortion, for example, the MDM2 Del1518 polymorphism and miR-196a (rs11614913). [9][10][11] Therefore, it is helpful to understand the causes of RM by studying whether some genes involved in breast cancer pathogenesis are associated with RM.…”
Section: Introductionmentioning
confidence: 99%